The Pattern of Lymphoma in East Malaysian Patients as Experienced in the University Hospital, Kuala Lumpur - Chai, S.P.; Peh, S.C.; Kim, L.H.; Lim, M.Y.; Gudum, H.R. (1999)
Lymphoma is a highly heterogeneous group of malignant disease. This study aimed to elucidate the pattern of lymphoma in the East Malaysian patient population. 107 cases of confirmed lymphomas from East Malaysian biopsy material were retrieved from the files of the Department of Pathology, University of Malaya, in the 3-year period between 198 1 to 1983. With the use of a panel of lymphoid antibodies, the disease was sub-classified using the Rye classification for Hodgkin's lymphoma (HL) and the REAL classification for non-Hodgkin's lymphoma (NHL). All of the cases were tested for the presence of the Epstein-Barr virus by EBER-ISH. There were 11 (10.3%) HL, 80 (74.7%) B-NHL and 16 (15%) T-NHL. The HL: NHL ratio was 1 :9. The most common tumour in children was Burkitt's lymphoma 711 3 (53.8%). In the adult group, there were 72/94 (76.6%) B-NHL {diffuse large cell type 51 (of which 2 were CD30+), Burkitt's lymphoma 8, follicular lymphoma 5, low grade MALT 2, mantle cell type 1 and not otherwise specified due to poor morphology 5 ), 13/94 (13.8%) T-NHL and 9/94 (9.6%) HL. Of the 9 adult HL, the most common subtype was nodular sclerosis (6,66.7%). The EBER positive rate in classical HL, T-NHL, BL and B-NHL were 33.3%, 56.3%, 60.0% and 3.1% respectively. In conclusion, the spectrum of lymphoma seen in East Malaysia was rather similar to West Malaysia except for the very low prevalence of peripheral T-cell lymphoma (PTCL) in Sarawak (3.3%).